2014
DOI: 10.1088/0004-637x/797/1/53
|View full text |Cite
|
Sign up to set email alerts
|

The Bones of the Milky Way

Abstract: The very long and thin infrared dark cloud "Nessie" is even longer than had been previously claimed, and an analysis of its Galactic location suggests that it lies directly in the Milky Way's mid-plane, tracing out a highly elongated bonelike feature within the prominent Scutum-Centaurus spiral arm. Re-analysis of mid-infrared imagery from the Spitzer Space Telescope shows that this IRDC is at least 2, and possibly as many as 5 times longer than had originally been claimed by Nessie's discoverers, Jackson et a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
183
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(196 citation statements)
references
References 50 publications
10
183
0
3
Order By: Relevance
“…Spatial, velocity and luminosity distributions used in the current model. We assumed the sun's vertical position to be z=0 pc and any change in this value, which Goodman et al (2014) suggested to be 25 pc, was found negligible at these scales. References: (1) , (2) Green & McClureGriffiths (2011), and (3) Pestalozzi et al (2007).…”
Section: Model For the 67 Ghz Methanol Maser Distribution In The Spimentioning
confidence: 99%
“…Spatial, velocity and luminosity distributions used in the current model. We assumed the sun's vertical position to be z=0 pc and any change in this value, which Goodman et al (2014) suggested to be 25 pc, was found negligible at these scales. References: (1) , (2) Green & McClureGriffiths (2011), and (3) Pestalozzi et al (2007).…”
Section: Model For the 67 Ghz Methanol Maser Distribution In The Spimentioning
confidence: 99%
“…The observed variation of Galactic latitude with repect to Galactic longitude can be understood in terms of the Sun's vertical displacement from the physical mid-plane (e.g., Hammersley et al 1995;Su et al 2016). Various observations have revealed that the Sun is about 10-30 pc above the physical mid-plane (e.g., Chen et al 2001;Reed 2006;Majaess et al 2009;Goodman et al 2014;Su et al 2016;Karim & Mamajek 2016).…”
Section: The Spiral Arm and Warp Of The Galactic Plane Traced By Co Ementioning
confidence: 99%
“…Nessie IRDC is rare object so far. Jackson et al (2010) obtained that the length of Nessie IRDC is 80 pc, but Goodman et al (2014) suggested that Nessie is probably longer than 80 pc. A similar filament of more than 50 pc length has been presented by Kainulainen et al (2011).…”
Section: Distribution Of Young Stellar Objectsmentioning
confidence: 99%